PENGARUH TERAPI BERMAIN MENGGUNAKAN PLAYDOUGH TERHADAP PENINGKATAN MOTORIK HALUS PADA ANAK PRASEKOLAH - Ferasinta, Ferasinta; Dinata, Endah Zulya (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2021)
Preschool children are children aged between 3-6 years, while at 4-6 years they usually attend kindergarten programs. It is hoped that they have been able to master several skills that require fine motor skills, such as using playdough by cutting in accordance with the fine motor development that must be achieved.This study aimed to determine the effect of playing therapy by using playdough with patterns cutting toward improving fine motor skills in preschool children in the Kedurang Health Center Work Area. This research design used a quasi experiment. A sample of 15 preschool children was taken by purposive sampling. The results of test analysis in the pre and post therapy intervention group playing playdough obtained a p-value of 0.000. There is a significant effect after playing playdough therapy on improving fine motor skills in preschool children. It is expected that the PAUD Nurul Amal Kab. South Bengkulu, the working area of the Kedurang Public Health Center, can be more creative in using learning methods such as playdough so that children's fine motor skills are more stimulated.Keywords:Â Preschool children, fine motor skills, Playdough